HSD10 disease in a female: A case report and review of literature. Issue 1 (15th September 2021) - Upadia, Jariya; Walano, Nicolette; Noh, Grace S.; Liu, Jiao; Li, Yuwen; Deputy, Stephen; Elliott, Lindsay T.; Wong, Joaquin; Lee, Jennifer A.; Caylor, Raymond C.; Andersson, Hans C.
Abstract: HSD10 disease is a rare X‐linked mitochondrial disorder caused by pathogenic variants in the HSD17B10 gene. The phenotype results from impaired 17β‐hydroxysteroid dehydrogenase 10 (17β‐HSD10) protein structure and function. HSD10 is a multifunctional protein involved in enzymatic degradation of isoleucine and branched‐chain fatty acids, the metabolism of sex hormones and neurosteroids, as well as in regulating mitochondrial RNA maturation. HSD10 disease is characterised by progressive neurologic impairment. Disease onset is varied and includes neonatal‐onset, infantile‐onset and late‐onset in males. Females can also be affected. Our index case is a 45‐month‐old female, who initially presented at 11 months of age with global developmental delay. She subsequently began to lose previously acquired cognitive and motor skills starting around 29 months of age. Brain MRI showed abnormalities in the basal ganglia indicative of possible mitochondrial disease. Urine organic acid analysis revealed elevations of 2‐methyl‐3‐hydroxybutyric acid and tiglyglycine. HSD17B10 gene sequencing revealed a likely pathogenic variant, NM_001037811.2:c.439C>T (p.Arg147Cys) inherited from her mother, expected to be causative of HSD10 disease. Her X‐chromosome inactivation study is consistent with a skewed X‐inactivation pattern. We report a female patient with HSD10 disease caused by a missense pathogenic variant, Arg147Cys in the HSD17B10 gene. The patient is the fifth severely affected female with this disease. This case adds to the small number of known affected families with this highly variable disease in the literature. These findings support the possibility of X‐inactivation patterns influencing the penetrance of HSD10 disease in females.